Growing Snowflakes—Unity in Difference - Tsun Haggarty, Holly; Sameshima, Pauline (Journal of the Canadian Association for Curriculum Studies, 2023)
An image of a snowflake adorns the cover of this issue. It also serves as a guiding metaphor for our editorial discussion. The twelve articles in this issue have been gathered over two years and come from varying perspectives on a variety of topics pertinent to the study of curriculum. Each article was developed using a distinct research practice. Like snowflakes, each article is unique, nuanced with individuality. And yet, like snowflakes, there are recognizable patterns that repeat across the articles of this issue. As we read about issues of colonial alienation of First Nation communities, COVID restrictions, financial literacy gaps and student distress, we observe recurring psychological and social processes. And these processes show fascinating parallels to the molecular dynamics of snow crystal formation! For example, we see the impact of the environment on the process of learning. We see the benefit of an interactive, adaptive, relational pedagogy centred on care. And we see the value of viewing things from a different perspective, through a different taxonomy. The metaphor of the snowflake shows us richness in diversity, and it also reminds us that a genuine conversation will reveal unity across difference.